Implementation of rural development programmes in Jammu and Kashmir - YOUNIS AHMAD SHEIKH (Journal of Governance and Public Policy, 2018)
Rural development is a holistic concept encompassing both natural and human resources development in an integrated manner. It aims at increasing the opportunities of all rural people in respect of health, knowledge, and skill development, income and participation in decision making and creating a conducive environment in reducing social and economic inequalities. Since Independence India has made a significant progress in rural development and In this connection large number of rural development programmes have been implemented by the concerned ministers and departments of the union and state governments in the area of education, health, drinking water, sanitation, transport and communication and supporting infrastructure, among others, have shown varying degree of response and performance at the grassroots level. The study is based on secondary data and focused on the rural development programmes which are implemented in the state of Jammu and Kashmir.